Excel macros for dummies - Alexander, Michael, 1972- (Hoboken, New Jersey : For Dummies, a Wiley Brand : John Wiley & Sons, Inc., 2015)
This book assumes no prior programming experience, so even programming novices can get up to speed quickly on the basics of Excel macros and the VBA language. Each chapter shows how to perform common tasks via Excel Macros. This lets the reader use the book as a handy reference where a common problem can be found in the book, and solved by plugging in the given macro. Each chapter will offer the reader practical macros that can be implemented right away. This book reinforces the reader's learning by presenting practical exercises, incrementally extending the reader's knowledge.
Includes index.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets -- Computer programs